Enhancing the stability of single-stranded DNA on gold nanoparticles as molecular machines through salt and acid regulation. Issue 36 (29th August 2019) - Zhang, Jianing; Jin, Jing; Du, Yanqiu; Zhou, Xiang; Liang, Haojun; Jiang, Wei
Abstract : Stable polyA–DNA–AuNPs incubated in an acidic buffer solution can construct a polyA–DNA based molecular machine. Abstract : DNA-functionalized gold nanoparticles (DNA–AuNPs) have shown great potential and exciting opportunities for constructing machine-like nanodevices. Nonthiolated DNA can be grafted onto gold surfaces via DNA bases, such as polyadenine (polyA)–DNA. The colloidal stability of polyA–DNA–AuNPs has a significant dependency on salt and pH that affects the assembly of AuNPs and their application in polyA–DNA molecular machines. High salt and low pH value contribute to the stabilization of polyA–DNA–AuNPs. In acid conditions, adenine can be protonated and becomes positively-charged, thus enhancing the adsorption of polyA–DNA onto the gold surface by electrostatic interactions; coordination of multiple interactions achieves a high DNA grafting density and colloidal stability. In addition, the length of adenine has an important effect on the efficiency of the DNA machine, while the length of thymine has little effect when the thymine length is less than or equal to seven. The assembly of AuNPs driven by dynamic polyA–DNA molecular machines was successfully accomplished with A5-DNA and A9-DNA. A moderate concentration of catalyst oligomer (50 nM) could improve the DNA hybridization efficiency. The A9-DNA based molecular machine is more efficient than the A5-DNA based one because of the larger amount of A9-DNA on the AuNPs, which increases the probability of collisions between complementary DNA strands. Therefore, polyA–DNA functionalized nanoparticles can be used as a basic unit to construct assembly-ordering structures and achieve dynamic molecular machines to be applied in the molecular diagnostics field.